Exploring the Role of Play Behaviors in the Links between Preschoolers' Shyness and Teacher-Child Relationships. Issue 2 (17th February 2022) - Sette, Stefania; Zava, Federica; Baumgartner, Emma; Laghi, Fiorenzo; Coplan, Robert J.
ABSTRACT: Research Findings : The goal of this study was to investigate the role of play behaviors in the links between child shyness and teacher-child relationship quality in preschool. Participants were 212 (102 girls) young children ( M = 58.32 months, SD  = 10.72) recruited from 10 classrooms in three preschools in central Italy. Parents evaluated children's shyness and teachers rated their relationships with children as well as play behaviors at preschools. Results from path analysis showed that shyness predicted the display of reticent behaviors (onlooking, unoccupied), which in turn, was associated with dependent teacher-child relationships. Shyness also predicted less social play, which in turn was related to less closeness with teachers. Practice or Policy : The findings provide evidence of the role of social play in impacting the quality of teacher relationships with shy preschool children. Teachers' understanding that children's characteristics may influence the quality of teacher-child relationships could be part of teacher training at preschool.